PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE COLLEGE BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 TANDUN KABUPATEN ROKAN HULU - Meli Sani, Afdia; Rahmi, Rahmi; Yunita, Alfi (Pendidikan Matematika, 2014)
ABSTRACTThis research background is the students do not active and do not comprehend about mathematical concept which illustrated by the lower score of mathematic that the eight grade students achieve at SMPN 1 Tandun. This study aims to determine how the activity and the students learning concept comprehension after using College Ball strategy for eight grade students at SMPN 1 Tandun. The type of the research is experimental research by random the subject. The population of the research consist of 7 classes of the eight grade students at SMPN 1 Tandun, in this research the researcher used random sampling to collect the sample, for both experimental and control class. The experimental class is VIIID class and the control class is VIIIB class. The instrumentations of the research are observation and test. The form of the test is essay with the reliability 0,86. The result based on observation is the increasing and decreasing of studentsâ activity. Furthermore, based on t test by using MINITAB which the confidence level 95% in hypothesis testing can be collected p-value 0,003, it is smaller than . thus, in brief the studentsâ mathematical concept comprehension by using College Ball strategy better than conventional learning for eight grade students at SMPN 1 Tandun, Rokan Hulu district.